Development of Physics Modules in OASIS-Based Work and Energy Subjects to Improve Students' Critical Thinking Ability - Ariyani, Nurul; Handhika, Jeffry; Kurniadi, Erawan (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2020)
This development research has a goal delevoping OASIS based module with the subject of work and energy to increase critical thinking skills of students. The development module contains the subject of work and energy, Oriented activities from an OASIS learning model (Orientation, Analysis, Synthesis, Investigation, Synergy), examples and exercises. The limited ADDIE model procedure which includes analysis, design, development, implementation. The development module is validated by 10 material and media experts. The results of validation are calculated using CVR and CVI calculations. CVI score of material experts is 0,8 and CVI score of media expers is 0,82, both of which are very suitable criteria. N-gain test was conduted in small classes to know the increase critical thinking skills of students. The n-gain result of critical thinking skill test was 0,66 in moderate category. Pretest homogenity test with Sig 0,535 and posttest homogeneity with Sig 0,678 greater than alpha 0,05. Meanwhile pretest normality test with Sig 0,638 and posttest normality test with Sig 0,180 greater than alpha 0,05. The t test paired sample test to know there’s an average difference in pretest and posttest , the value Sig 0,000 smaller than alpha 0,05. Meanwhile the result of student responses showed 73,3% in good category. In conclusion, effectiveness of the application of an OASIS based physics module is able to increase critical thinking skills of students.Keywords: Module, OASIS Based, Critical Thinking Skill